KOMUNIKASI EFEKTIF PADA ANAK USIA DINI DALAM PENGENALAN AJARAN AGAMA HINDU - Dharma Putra, Anggara Putu; Tagel, Dewa Putu (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2019)
The process of communication can occur anywhere such as home, office, hospital, and school. Effective communication is the flow of information or messages in two directions between the communicator and the communicant as well as the information is equally addressed in accordance with the expectations of both actors (communicator and communicant). From the description above, the writer wants to conduct research on ?Effective Communication In Early childhood In the Introduction of the Hindu Religion?. Based on the description of the background din above, the writer can formulate the following problem formulation: 1) How personal communication in the introduction of the teachings of Hinduism? 2) How Effective Communication In Early Childhood In The Introduction Of The Teachings Of Hinduism? 3) How the impact of Effective Communication caused in early childhood in the introduction of the Teachings of the Teachings of Hinduism?                To dissect the problems in this study used 3 kinds of theories, namely 1) the Theory of interaction patterns of the relationship to determine the personal communication in the introduction of the teachings of Hinduism, 2) Theory of Effective Communication to determine the effectiveness of communication in early childhood in the introduction of the teachings of the Hindu Religion, 3) the Theory of Expectation Value to determine the impact of the introduction of the teachings of Hinduism in early childhood.After getting the accurate data, followed by analyzing the data obtained using the technique of data analysis, inter-personal communication is a form of communication between teachers and students, students with fellow students, teachers with parents of students as well as students with parents that happens to the equation of perception in penyemapian knowledge. Effective communication gives an overview of the objectives and results to be achieved by the school maupaun teaching teachers in the classroom Impact the internal is the ability to understand themselves and responsible for his own life. External impact is the result of the processing of the knowledge process in each individual that arises through the action.